Comparison Analysis Of Recovery Mechanism At Mpls Network - Mohammad Yanuar Hariyawan (Institute of Advanced Engineering and Science, 2011)
Multi-protocol Label Switching (MPLS) has become an attractive technology of choice for Internet backbone service providers. MPLS features the ability to perform traffic engineering and provides support for Quality of Service traffic provisioning. To deliver reliable service, MPLS requires a set of procedures to provide protection for the traffic carried on Label Switched Paths (LSP). In this case Lable Switched Routers (LSRS) supports recovery mechanism when failure happened in the network.This paper studied about performance from usage of different techniques that can be used to reroute traffic faster then the current IP rerouting methods in the case of a failure in a network. Local rerouting, fast reroute one to one backs up, Haskin, PSL oriented path protection and 1+1 path protection recovery mechanism was compared by given of aggregate traffic which has self-similarity character. Packet drop, rejection probability, recovery time, service disruption time and pre-reserved resources backup will be made as comparator parameter with various bitrate and different position of link failure. Packet loss, rejection probability, recovery time and service disruption time at five recovery mechanisms influenced by position of link failure to ingress. 1+1 path protection mechanism has least packet drop, but costliest way to do recovery in the case of usage resources, as traffic is sent simultaneously in two paths which disjoint. Fast reroute one to one backup is quickest way to operate protection switching recovery after 1+1 path protection mechanism. Keywords: MPLS, recovery, rerouting, self-similar traffic, protection switchingDOI:http://dx.doi.org/10.11591/ijece.v1i2.84